1994
DOI: 10.1021/bi00209a005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a water molecule in the active-site of bacteriorhodopsin: hydrogen bonding changes during the primary photoreaction

Abstract: FTIR-difference spectroscopy in combination with site-directed mutagenesis has been used to investigate the role of water during the photocycle of bacteriorhodopsin. At least one water molecule is detected which undergoes an increase in H-bonding during the primary bR-->K phototransition. Bands due to water appear in the OH stretch region of the bR-->K FTIR-difference spectrum which downshift by approximately 12 cm-1 when the sample is hydrated with H2(18)O. In contrast to 2H2O, the H2(18)O-induced shift is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 45 publications
(66 reference statements)
7
117
1
Order By: Relevance
“…Knowledge of dynamics of hydration at a molecular level is thus of considerable importance in understanding the cellular structure and function (Crowe and Crowe, 1984;Rand and Parsegian, 1989;Ho and Stubbs, 1992;Ho et al, 1994;Fischer et al, 1994;Kandori et al, 1995;Sankararamakrishnan and Sansom, 1995;Häussinger, 1996;Israelachvili and Wennerströ m, 1996;Nishimura et al, 1997;Hummer et al, 2001;Mentré, 2001). As mentioned earlier, REES is based on the change in fluorophore-solvent interactions in the ground and excited states brought about by a change in the dipole moment of the fluorophore upon excitation, and the rate at which solvent molecules reorient around the excited state fluorophore.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of dynamics of hydration at a molecular level is thus of considerable importance in understanding the cellular structure and function (Crowe and Crowe, 1984;Rand and Parsegian, 1989;Ho and Stubbs, 1992;Ho et al, 1994;Fischer et al, 1994;Kandori et al, 1995;Sankararamakrishnan and Sansom, 1995;Häussinger, 1996;Israelachvili and Wennerströ m, 1996;Nishimura et al, 1997;Hummer et al, 2001;Mentré, 2001). As mentioned earlier, REES is based on the change in fluorophore-solvent interactions in the ground and excited states brought about by a change in the dipole moment of the fluorophore upon excitation, and the rate at which solvent molecules reorient around the excited state fluorophore.…”
Section: Resultsmentioning
confidence: 99%
“…This makes REES and related techniques extremely useful in biology since hydration plays a crucial modulatory role in a large number of important cellular events such as lipid-protein interactions 22 and ion transport. [23][24][25] We have previously shown that REES and related techniques (wavelength-selective fluorescence approach) serve as a powerful tool to monitor organization and dynamics of membranebound probes and peptides. In one of our studies, the wavelength-selective fluorescence characteristics of the widely used membrane probe N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)-1,2-dipalmitoyl-sn-glycero-3-phosphoethanolamine (NBD-PE), when bound to model membranes of dioleoyl-sn-glycero-3-phosphocholine (DOPC), was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Such bands were first detected in the FTIR difference spectra of BR by the A. Maeda's group in the OD stretching region using D 2 due to an increase in hydrogen bonding of a single water molecule [87,88]. The high frequency of this OH stretch is indicative of "dangling" OH groups which lacks the normal hydrogen bonding found in bulk water.…”
Section: Structural Changes Of Internal Water Moleculesmentioning
confidence: 98%
“…22). In general, site-directed mutagenesis can provide information about the approximate location of these waters in the BR structure [87,123,153,156] while polarized FTIR difference spectroscopy can provide information about thee orientation of the OH dipole moments [111]. In addition to the internal water molecules that give rise to specific OH vibrational water bands, FTIR differences also reveal broad continuum IR absorbance that is associated with networks of strongly hydrogen bonded water and other OH groups [251].…”
Section: Structural Changes Of Internal Water Moleculesmentioning
confidence: 99%